THE RELEVANCE OF A COMPREHENSIVE ANALYSIS OF MEDICAL AND DEMOGRAPHIC PROBLEMS IN CONNECTION WITH THE HARMFUL EFFECTS ON HUMANS OF ENVIRONMENTAL FACTORS IN KUZBASS - Петров, Андрей Георгиевич; Семенихин, Виктор Андреевич; Хорошилова, Ольга Владимировна; Филимонов, Сергей Николаевич; Сашко, Юлия Александровна (Medicine in Kuzbass, 2022)
The goal is to identify patterns of changes that have occurred with medical and demographic indicators in connection with the harmful effects on humans of environmental factors in Kuzbass. Material and methods. The analysis uses data from official statistics of the Unified Interdepartmental Information and Statistical System (EMISS) in Kuzbass and the Russian Federation, State reports «On the state of sanitary and epidemiological well-being of the population of Kuzbass in 2021» and «On the state of sanitary and epidemiological well-being of the population in the Russian Federation in 2020». Results. During the analyzed period in the Russian Federation and in Kuzbass, due to the harmful effects of environmental factors on humans in 2021, a significant decrease in the population continues in relation to 2020. The population in Kuzbass decreased by 24,408 people. This phenomenon is caused by both natural and migration population decline, which has been registered since 2011. At the same time, the leading role in the population decline belongs to the natural population loss, which has increased in recent years against the background of a decrease in the migration loss of the population. Currently, the medical and demographic situation in Kuzbass remains more unfavorable than the average in the Russian Federation. Conclusion. In Kuzbass, in comparison with the Russian Federation, the mortality rates of the population are higher and life expectancy is lower, and there are higher mortality rates of the population from most of the most common causes of death than in the Russian Federation. This phenomenon is associated with the current trends of demographic processes in the region. One of the most important social levers is the activity of healthcare. However, in order to increase the effectiveness of this activity, it is necessary to concentrate efforts on key issues in order to solve the whole complex of problems that have arisen in the field of public health. Medical and demographic studies of this problem can contribute to the activation of health care activities in conducting an effective demographic policy.